Biostimulant influence on morphological and agrochemical characters in banana (Musa AAA cv. Williams) - Ugarte-Barco, Francisco Andrés; Zhiñin-Huachun, Iván Armando; Hernández-Pérez, Ricardo (REVISTA TERRA LATINOAMERICANA, 2022)
Some of the limitations for plant acclimatization in vitro in banana cultivation have been poor rooting and slow leaf development, which affect survival in the f ield under stress conditions after planting. The aim of this study is to compare seedling response of Musa cv. Williams treated with biostimulants and commercial de-stressing agents. Thirty days after inoculation, pseudostem diameter (cm), fresh plant mass (g), fresh root mass (g), root number, soil-plant analysis development (SPAD) index, edaphic ionic content and foliar content (pH, CE, NO3-, K+, Na+ and Ca2+) were evaluated. Preliminary results indicated, that StresSal® and (StresSal® + Equilibrium®) showed signif icantly greater pseudostem diameter. The highest radical fresh mass corresponded to (Inicium® + StresSal®). Root number was not signif icantly different. The SPAD index was elevated when StresSal® was applied alone or with Equilibrium®. The treatment (Inicium®+StresSal®) contributed to higher soil acidity. Conductivity (CE), K+ and Na+ were higher when Inicium® + Pro- Fulvic® were applied. As NO3- levels increased with Inicium®, Ca2+ ions decreased signif icantly in soil with Inicium® + StresSal®. Regarding foliar content, the highest pH corresponded to Inicium®, conductivity (CE) was higher with StresSal® and Inicium® + StresSal®, without difference with the control. An increase in NO3- was found with Inicium® + StresSal®. While Na+ and Ca2+ were signif icantly higher with Inicium® + Pro-Fulvic®.